GENDER EQUALITY AND WOMEN’S POWER IN AMERICAN INDIAN TRADITIONAL CULTURE IN ZITKALA-SA'S SHORT STORIES - Rorintulus, Olga Anneke (Humanus, 2018)
This article intends to reveal gender equality and women’s power in American Indian traditional culture before they were assimilated in white American society in the late nineteenth century as reflected in Zitkala-Sa’s short stories, Impressions of an Indian Childhood, The Soft Hearted Sioux and A Warrior Daughter. This study is a qualitative research that applies feminist literary approach which uses liberal feminist theory for the data analysis. This study shows that American Indian women enjoyed gender equality in traditional American Indian culture that had complementary gender relation. American Indian women had power and equal rights to be warriors and leaders in their society.Keywords: gender role, American Indian women, complimentary relation.KESETARAAN GENDER DAN KUASA PEREMPUAN DALAM BUDAYA TRADISIONAL INDIAN AMERIKA DALAM CERITA-CERITA PENDEK ZITKALA-SA AbstrakArtikel ini bertujuan untuk mengungkapkan kesetaraan gender dan kuasa perempuan Indian Amerika dalam budaya tradisional masyarakat Indian Amerika sebelum mereka mengalami program asimilasi yang bertujuan untuk menyatukan masyarakat Indian Amerika dengan masyarakat kulit putih di akhir abad ke-19 seperti yang terefleksi dalam cerita pendek Zitkala-Sa, Impressions of an Indian Childhood,The Soft Hearted Sioux  dan A Warrior Daughter. Artikel ini ditulis dengan mengunakan metode kualitatif dan menerapkan pendekatan kajian feminisme sastra dengan teori feminisme liberal. Hasil dari analisa ini menunjukkan bahwa perempuan Indian Amerika telah menikmati kesetaraan gender dalam budaya tradisional Indian Amerika yang memiliki relasi gender yang saling melengkapi dan mereka memiliki kuasa dan hak yang setara dengan laki laki Indian Amerika untuk menjadi prajurit dan pemimpin dalam masyarakat Indian Amerika.Kata kunci: peran gender, Perempuan Indian Amerika, relasi setara